Ba6(MN4)N2–x (M = MoVI/TaV), a Subvalent Nitridometalate with Perovskite‐like Crystal Structure. Issue 3 (8th November 2018) - Wörsching, Matthias; Fricke, Sarah‐Kristin; Minár, Ján; Niklaus, Robin; Hoch, Constantin
Abstract : The subvalent nitridometalate Ba6 [(Mo1– x Ta x )N4 ]N0.86 was prepared from mixtures of Mo powder with Ba, Na, and Ba2 N at 600 °C in Ta ampoules. It crystallizes in space group Cmcm with a = 11.672(3), b = 10.177(2) and c = 10.8729(19) Å. Its crystal structure exhibits an orthorhombically distorted Perovskite topology with [Ba6 N] building units forming the ReO3 ‐type lattice via common vertices, and the nitridometalate anions occupying half of the available distorted cuboctahedral interstices. [ M N4 ] anions show statistically mixed occupancy of M by Mo VI and Ta V . They show no notable deviation from nitridometalate anions in known ionic nitridomolybdates and ‐tantalates, and the metrics of the [Ba6 N] octahedra correspond to those found in similar subvalent compounds. The nitrogen atom position centering the [Ba6 N] octahedra is underoccupied. Band structure calculations corroborate the subvalent character of the compound and the two individual anionic structural building units. Abstract :